2019
DOI: 10.3390/su11102941
|View full text |Cite
|
Sign up to set email alerts
|

Regional Integration in the Inter-City Technology Transfer System of the Yangtze River Delta, China

Abstract: Recently, the Chinese government decided to support the integrated development of the Yangtze River Delta (YRD) in a national strategic way. On this background, this paper investigates the regional integration in the technology transfer system of the YRD based on patent transfer from three levels: overall, technology supply chain, and technology sales chain. It also uses the modularity maximization method to detect the community structure of the inter-city patent transfer network in China. The results show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 64 publications
(100 reference statements)
0
9
0
Order By: Relevance
“…The YRD region, located on the east coast of China, is strategically important because it is one of the most developed urban agglomerations and considered a major engine of China's economic and urban development in the last three decades (Li and Phelps, 2019). The YRD region, which leads in terms of innovation-driven development, comprises three provinces and one municipality: Jiangsu, Zhejiang, Anhui and Shanghai (Duan et al , 2019). It is a potential source of global knowledge linkages and the most developed region in China (Wang and Shen, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The YRD region, located on the east coast of China, is strategically important because it is one of the most developed urban agglomerations and considered a major engine of China's economic and urban development in the last three decades (Li and Phelps, 2019). The YRD region, which leads in terms of innovation-driven development, comprises three provinces and one municipality: Jiangsu, Zhejiang, Anhui and Shanghai (Duan et al , 2019). It is a potential source of global knowledge linkages and the most developed region in China (Wang and Shen, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Shanghai seems to be both a local decentralized agency and a national hub, a more balanced broker area. Duan et al [41] discussed the structural spatial characteristics of the technology transfer network in the Yangtze River Delta from three aspects of the overall, technology supply chain, and technology sales chain, and used the block model to explore the community characteristics of China's intercity technology transfer network. Based on the patent transfer data of the State Intellectual Property Office from 2000 to 2015, Zhang et al [42] constructed China's inter-city technology transfer network, and the results showed that there was a certain geographical differentiation in China's inter-city technology transfer.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Its spatial carriers mainly include metropolitan areas, urban agglomerations, megaregions, and other urban spatial organizations. There has been a renaissance in the regional policies and planning across China that echo national strategies and highlight inter-jurisdictional cooperation and integration [33,34]. To some extent, these practices indicate a transition in regional governance from territorial competition to regional coordination, in which adjacent municipalities are encouraged to transcend jurisdictional boundaries and function in coordinated ways as unitary megaregions.…”
Section: Integrative Process In the Cyrmmentioning
confidence: 99%